Cutting Wood Origin and Indole Butyric Acid Influence Success of Liberica Coffee Cuttings (Coffea Liberica W. Bull Ex. Hier) - Novie Pranata Erdiansyah; Inung Pinata Rokhani; Sriyanto Waluyo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Liberica coffee can be grown in peatland and has a specific flavor. To anticipate high demand of Liberica coffee product, it is very important to support the availability of high quality seedlings that need effective multiplication method of superior genotypes. This study aimed to investigate the effect of indole-butyric acid (IBA) concentration and cuttings wood origin and their interaction in the success of Liberica coffee cuttings. This research was held at Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute, designed using randomized complete block in factorial with two factors consisted of cutting wood origin and concentration of IBA. First factor was cuttings wood origin consisted of the tip, middle, and base, while second factor consisted of the concentration of IBA i.e. 0, 1500, 3000, and 4500 ppm. The results showed that the end of the shoots aged of 4-6 months were better part of shoot for cutting material. Percentage of the grown cutting reach up to 80%, while the middle and base part of shoots had a fairly low percentage of grown cutting, less than 43%. IBA a tended to increase rooted cuttings number. Combined treatment between cuttings material origin in the middle part with the IBA concentration of 4500 ppm showed the best root growth.